Survival, trust, and compassion: persistent HIV prevention concerns faced by Black sexual and gender minority communities in the US South – a qualitative study - Elkins, Jesse Strunk; Dale, Ian; Okumu, Eunice; Zinck, Matthew; Golin, Carol; McCrimmon, Jordyn; Esposito, Maria; Duguid, Isabelle T.; Craven, Dalton M.; Onyeama, Ujunwa; Marin-Cespedes, Sebastian; Diggs, Alicia; et al. (Frontiers in Public Health, 2025)
BackgroundMembers of Black sexual and gender minority (BSGM) groups in the Southern US experience disparities across all pillars of the HIV prevention continuum. Social network strategy (SNS) is an intervention that trains people with reasons to test for HIV to reach out to peers to increase HIV testing and may improve uptake of pre-exposure prophylaxis (PrEP). We conducted formative research to design an enhanced SNS to implement within partner services.MethodsIn 2022–2024, we conducted four focus groups among HIV public health services staff and 12 in-depth interviews with local health department officials, clinicians, and community-based organization leaders. In addition, we interviewed four BSGM community members who recently used prevention services (i.e., testing or PrEP). Focus groups and interviews were transcribed and iteratively coded. Themes included salient barriers and facilitators to HIV services and mapped to a modified socio-ecological model after analysis. Narratives from the four BSGM were integrated with the summary analyses from HIV service providers.ResultsService providers and community members identified persistent barriers to HIV prevention services: (1) basic human needs for survival and (2) lack of compassion within the healthcare system. Inadequate living necessities (e.g., housing and transportation), education, mistrust, stigma, and discrimination limit HIV prevention service use. Conversely, wrap-around services, transparency, representation, and compassionate care facilitate service access.ConclusionEnhancing HIV prevention services for BSGM groups necessitates reducing healthcare access barriers and leveraging facilitators. Our findings informed an enhanced SNS intervention to increase HIV testing, prevention, and care linkage among BSGM in the Southern US.